MODELING METHOD IN STOCK MANAGEMENT HIERARCHICAL LOGISTICS SYSTEMS - POTAPOVA, Nadiia; VOLONTYR, Ludmila (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The work highlights the issue of using the modeling method in inventory management of hierarchical logistics systems. The issue of the necessity of inventory management modeling as one of the key parameters of distribution logistics is substantiated. It has been proven that the hierarchical logistics system can generate flow processes according to Poisson’s law, which makes it possible to apply the theory of mass service systems in the formalization of the processes of incoming supplies of resources to replenish the stocks of the logistics center with further distribution of flows among regional branches. This method is based on obtaining optimal characteristics of the intensity of supply of resources in the section of a specific nomenclature, subject to restrictions on available working capital and the formation of a reserve stock for maintenance of repair works.